Isotopic evidence for dietary ecology of late Neandertals in North-Western Europe. (8th August 2016) - Wißing, Christoph; Rougier, Hélène; Crevecoeur, Isabelle; Germonpré, Mietje; Naito, Yuichi I.; Semal, Patrick; Bocherens, Hervé
Abstract: The Late Pleistocene site "Troisième caverne" of Goyet (Belgium) has yielded the broadest set of Neandertal remains in North-Western Europe and is associated with a rich and diverse large mammal assemblage. We reconstructed the dietary ecology at the site using stable isotope tracking (δ 13 C and δ 15 N) of bone collagen. The δ 13 C and δ 15 N values of all species are consistent with those observed in other "mammoth steppe" sites. The relative contribution of potential prey species to the diet of carnivores (including Neandertals) was evaluated using a Bayesian model. The distribution of individuals from herbivorous species and carnivorous ones was determined through cluster analysis in order to identify ecological niches, regardless of the individual species attribution. The Neandertals within the predator guild and the mammoth and reindeer as representatives of the herbivores occupied the most specific and most narrow ecological niches. The "Troisième caverne" of Goyet can be regarded as a key site for the investigation of Late Pleistocene Neandertal ecology north of the Alps.